PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP FINANCIAL DISTRESS DAN SIKLUS HIDUP PERUSAHAAN - Risa Wahyuni EDT; Maretha Primadyan; Winona Kumara Dewi (Jurnal Ilmiah Global Education, 2023)
The purpose of this study is to test and analyze the effect of Corporate Social Responsibility on Financial Distress and Firm Life Cycle. The researcher used the sampling method by Purposive Sampling. The data collection technique in this study used documentation techniques by collecting financial reports and annual reports of mining companies from the Indonesian Stock Exchange. Based on the results of the study, it can be concluded that Corporate Social Responsibility has a positive effect on Financial Distress and Corporate Social Responsibility has no effect on the Firn Life Cycle. Where the value of R Square of Corporate Social Responsibility on Financial Distress is 0,109 or the effect is 10,9% and the value of R Square of Corporate Social Responsibility on the Firm Life Cycle is 0,032 or the effect is 3.2%, the rest is influenced by other variables not described in this research.